Budget Communication, Final Authority, And Negotiation On Budgetary Proposal : An Experimental Study - Kusufi, Muhammad Syam (Pusat P2M Politeknik Negeri Batam, 2023)
This study aims to investigate the relation between budget communication, final authority and negotiation on budget setting which analyzed by Agency Theory. This research used 2x3 between subject experimental design of budget communications and final authority treatments. The results of this study show that less slack is created when budget proposal requires a factual assertion, but it's not when manager not requires factual assertion. Meanwhile, in final authority condition, manager creates budget slack more when they have final authority than owner's authority. This study show an evidence that there is no significant interaction between budget communication and final authority in creating budget slack. Additionally, this study finds that negotiation can influence manager's performance although it's measured by budget slack or output of production. Negotiation can reduce budget slack. The performance test (which is measured by ability of manager to make product) show that as a whole is not have difference significantly. Meanwhile, for budget slack show that slack in No Factual Assertion treatment is higher than Factual Assertion treatment. Keywords: Participative Budgeting, Budget Communication, Final Authority, Negotiation, Budget Slack, Manager's Performance.